2020
DOI: 10.1093/ejcts/ezaa040
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative localization of cardiac conduction tissue regions using real-time fibre-optic confocal microscopy: first in human trial

Abstract: OBJECTIVES The aim of this study was to evaluate the feasibility and safety of fibre-optic confocal microscopy (FCM) using fluorescein sodium dye for the intraoperative location of conduction tissue regions during paediatric heart surgery. METHODS The pilot study included 6 patients undergoing elective surgery for the closure of isolated secundum atrial septal defect aged 30 days to 21 years. FCM imaging was integrated within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“… 38 , 39 Fiber optics confocal microscopy, as one example, has been used during open heart surgery to distinguish tissue regions. 18 However, due to significant financial costs and complexity associated with refining their use and deploying these technologies in the operating room, they have yet to see widespread adoption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 38 , 39 Fiber optics confocal microscopy, as one example, has been used during open heart surgery to distinguish tissue regions. 18 However, due to significant financial costs and complexity associated with refining their use and deploying these technologies in the operating room, they have yet to see widespread adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Though these approaches have shown promise due to their comparatively high imaging resolution and ability to discern different tissue types within the heart, including nodal tissue regions, the significant financial costs, and complexity associated with their use have hindered widespread implementation. 18 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A focus of our review was on clinical translation of catheterized fiber-optics confocal microscopy. Feasibility of fiber-optics confocal microscopy to image through the endocardial layer in the atrial and ventricular myocardium was demonstrated in in-situ canine [59], neonatal ovine [60], and neonatal human hearts [188]. For myocardial imaging in the adult human heart, the approach must contend with the endocardial thickness.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 6 , 7 Clinical studies and related research with FCM have shown the ability to identify conductive tissue regions during congenital heart surgery, e.g., the sinoatrial and atrioventricular nodes. 8 , 9 Although these technologies have been shown to provide useful information during cardiac procedures, the significant cost and technical complexity associated with their implementation hinder widespread adoption. Additionally, shallow imaging field depths limit the application of these technologies to only a few specific use cases in the heart.…”
Section: Introductionmentioning
confidence: 99%